Effects of Shape and Size of Cobalt Phosphate Nanoparticles against Acanthamoeba castellanii - Anwar, Ayaz (2019)
T4 genotype Acanthamoeba are opportunistic pathogens that cause two types of infections, including vision-threatening Acanthamoeba keratitis (AK) and a fatal brain infection known as granulomatous amoebic encephalitis (GAE). Due to the existence of ineffective treatments against Acanthamoeba, it has become a potential threat to all contact lens users and immunocompromised patients. Metal nanoparticles have been proven to have various antimicrobial properties against bacteria, fungi, and parasites. Previously, different types of cobalt nanoparticles showed some promise as anti-acanthamoebic agents. In this study, the objectives were to synthesize and characterize the size, morphology, and crystalline structure of cobalt phosphate nanoparticles, aswell as to determine the effects of different sizes of cobalt metal-based nanoparticles against A. castellanii. Cobalt phosphate octahydrate (CHP), Co3(PO4)2.8H2O, was synthesized by ultrasonication using a horn sonicator, then three different sizes of cobalt phosphates Co3(PO4)2 were produced through calcination of Co3(PO4)2.8H2O at 200 ˚C, 400 ˚C and 600 ˚C(CP2, CP4,CP6). These three types of cobalt phosphate nanoparticleswere characterized using a field emission scanning electronmicroscope (FESEM), energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) analysis. Next, the synthesized nanoparticles were subjected to biological assays to investigate their amoebicidal, amoebistatic, anti-encystation, and anti-excystation effects against A. castellanii, as well as cell cytotoxicity. The overall results showed that 1.30 ± 0.70 μm of CHPmicroflakes demonstrated the best anti-acanthemoebic effects at 100 μg/mL, followed by 612.50 ± 165.94 nm large CP6 nanograins. However, amongst the three tested cobalt phosphates, Co3(PO4)2, the smaller nanoparticles had stronger antiamoebic effects against A. castellanii. During cell cytotoxicity analysis, CHP exhibited only 15% cytotoxicity against HeLa cells, whereas CP6 caused 46% (the highest) cell cytotoxicity at the highest concentration, respectively. Moreover, the composition and morphology of nanoparticles is suggested to be important in determining their anti-acathamoebic effects. However, the molecular mechanisms of cobalt phosphate nanoparticles are still unidentified. Nevertheless, the results suggested that cobalt phosphate nanoparticles hold potential for development of nanodrugs against Acanthamoeba.